Penerapan Model Talking Stick untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas V SDN Randuagung 02 pada Materi Persiapan Kemerdekaan Indonesia - Sudyastuti, Ety (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2018)
The aim of study was to describe the application of Talking Stick model, student activity when applied Talking Stick model, and student learning result after applied Talking Stick model. This study uses a classroom action research design (PTK) with two cycles and each cycle has two meetings. The data were collected by observation techniques and field notes. The data collection instrument uses observation and test sheets. The collected data is analyzed descriptively qualitative and quantitative. The results showed that the application of Talking Stick model can improve student activity and learning outcomes in learning IPS material Preparation of Indonesian Independence SDN 1 Randuagung. Class V student learning activity in IPS study increased by 10.1%. The learning outcomes of grade V students in IPS study increased after applied Talking Stick model. Students who have completed learning criteria successively in the first cycle of meeting 1 to cycle II meeting 2 as many as 17 students or 63%, 20 students or 74%, 22 students or 81.4%, and 25 students or 92.5%.